Analysis of Fish Samples for Heavy Metals And Total Hydrocarbon Content From Okrika And Bonny Rivers In Rivers State, Nigeria - Onye, Chizitere Chris; Nwajideobi, Ijeoma Comfort Ozuah (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
This study examines the concentrations of heavy metals (cadmium [Cd), chromium [Cr), lead (Pb), arsenic (As), and nickel (Ni) and total hydrocarbon content (THC) in three fish species (Illish, Mullet, and Tilapia) from Okrika and Bonny Rivers in Rivers State, Nigeria. Fresh fish samples were collected and analyzed to assess their contamination levels. Heavy metals were determined using Atomic Absorption Spectrophotometry (AAS), while THC was analyzed using standard extraction techniques and Gas Chromatography-Mass Spectrometry (GC-MS). The results revealed that the concentrations of heavy metals in fish species exceeded permissible limits set by the Food and Agriculture Organization (FAO) and World Health Organization (WHO) in several instances. Notably, Mullet Fish from Okrika River exhibited significantly elevated levels of Cd (2.0±0.36 mg/kg), Cr (2.02±0.12 mg/kg), Pb (10.25±1.03 mg/kg), and As (2.5±0.37 mg/kg). Similarly, fish from Bonny River also displayed high levels of contaminants, albeit generally lower than those from Okrika River. The THC levels, while below the Department of Petroleum Resources (DPR) threshold of 50 mg/kg, reflected ongoing hydrocarbon pollution, with Mullet Fish from Okrika River recording 3.08±0.06 mg/kg. Comparative analysis with existing literature highlights the severe pollution levels in these rivers, likely driven by industrial discharges, urban runoff, and oil-related activities. Species-specific trends indicate higher contaminant bioaccumulation in Mullet Fish, attributed to their benthic feeding habits. The study underscores significant environmental and public health concerns, given the reliance of local communities on these rivers for fish consumption. Urgent interventions, including stricter pollution control, sustainable waste management, and regular monitoring, are recommended to mitigate the risks posed by heavy metal and hydrocarbon contamination in aquatic ecosystems.